Odpowiedź :
11.
a)
[tex]2x-\frac{1}{2}(3x-2) = \frac{7}{4}-x \ \ |\cdot 4\\\\8x-2(3x-2)=7-4x\\\\8x-6x+4 = 7-4x\\\\2x+4x = 7-4\\\\6x = 3 \ \ /:3\\\\\boxed{x = \frac{1}{2}}[/tex]
b)
[tex]3\frac{1}{3}x + 8 = 4\frac{2}{5}x-8\\\\\frac{10}{3}x+8 = \frac{22}{5}x-8 \ \ |\cdot15\\\\50x + 120 + 66x-120\\\\50x-66x = -120-120\\\\-16x = -240 \ \ /:(-16)\\\\\boxed{x = 15}[/tex]
Odpowiedź:
2x - 1/2(3x - 2) = 7/4 - x
2x - 1 i 1/2x + 1 = 1 i 3/4 - x
2x - 1 i 1/2x + x = 1 i 3/4 - 1
1 i 1/2x = 3/4
3/2 x = 3/4
x = 3/4 * 2/3
x = 1/2
3 i 1/3x + 8 = 4 i 2/5x - 8
10/3x + 8 = 22/5x - 8
50x + 120 = 66x - 120
50x - 66x = -120 - 120
-16x = - 240
x = -240/ :(-16)
x = 15